MATERNAL FACTORS ASSOCIATED WITH LOW BIRTH WEIGHT NEWBORN IN A TERTIARY CARE CENTRE OF SOUTHERN RAJASTHAN - MALVIA, SUNNY; RAJWANIYA, DINESH; JAKHAR, SURESH; KAUR, JOBANJEET (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Low birth weight is defined as weight at birth of <2500 g as per the World Health Organization. Low birth weight (LBW) newborns have higher risk of morbidity and mortality during perinatal period. The aim of the study was to ascertain the maternal factors leading to low birth weight in newborns. Methods: A cross-sectional study was done for a period of 1 year. Mothers delivering term LBW babies from singleton pregnancy were taken as cases and mothers with term, normal weight newborns from singleton pregnancy were termed as control group. Babies with congenital malformations, still births, and multiple gestations were excluded from the study. Written consent for the study in local language from each subject was taken. Institutional ethical clearance was obtained. Results: One thousand two hundred and fifty-six babies were born during the study period and out of these 258 babies were weighing <2.5 kg thus the incidence of LBW <2.5 kg was 20.54%. Young maternal age (<30 years) and multi parity (≥3) had significantly increased LBW incidence of 28.7% and 32%, respectively. Pregnancy complications such as anemia and pre-eclampsia had significantly increased incidence of LBW newborn of 33.455 and 29.1%, respectively. Conclusion: Pregnancy-related anemia and hypertension are an important risk factor for LBW. Young maternal age pregnancy and poor ante natal visits also contribute toward LBW.